Localisation of a gene implicated in a severe speech and language disorder. - Fisher, S; Vargha-Khadem, F; Watkins, K; Monaco, A; Pembrey, M (1998)
Between 2 and 5% of children who are otherwise unimpaired have significant difficulties in acquiring expressive and/or receptive language, despite adequate intelligence and opportunity. While twin studies indicate a significant role for genetic factors in developmental disorders of speech and language, the majority of families segregating such disorders show complex patterns of inheritance, and are thus not amenable for conventional linkage analysis. A rare exception is the KE family, a large three-generation pedigree in which approximately half of the members are affected with a severe speech and language disorder which appears to be transmitted as an autosomal dominant monogenic trait. This family has been widely publicised as suffering primarily from a defect in the use of grammatical suffixation rules, thus supposedly supporting the existence of genes specific to grammar. The phenotype, however, is broader in nature, with virtually every aspect of grammar and of language affected. In addition, affected members have a severe orofacial dyspraxia, and their speech is largely incomprehensible to the naive listener. We initiated a genome-wide search for linkage in the KE family and have identified a region on chromosome 7 which co-segregates with the speech and language disorder (maximum lod score = 6.62 at theta = 0.0), confirming autosomal dominant inheritance with full penetrance. Further analysis of microsatellites from within the region enabled us to fine map the locus responsible (designated SPCH1) to a 5.6-cM interval in 7q31, thus providing an important step towards its identification. Isolation of SPCH1 may offer the first insight into the molecular genetics of the developmental process that culminates in speech and language.